ANALISIS ANGKA LEMPENG TOTAL BAKTERI DAN KEBERADAAN SALMONELLA TYPHI PADA SAUS CABAI JAJANAN PEDAGANG DI LINGKUNGAN UNIVERSITAS PALANGKA RAYA - Nazhifah, Annida Kholifatun; Furtuna, Dewi Klarita; Praja, Rian Ka; Martani, Natalia Sri; Ratnasari, Arini (Program Studi Teknologi Laboratorium Medis, 2024)
. Chilli sauce is a food additive that is served by many food vendors. Chili sauce could be contaminated by microbial contamination. To know food safety according to Peraturan Badan Pengawas Obat dan Makanan Nomor 13 Tahun 2019 Tentang Batas Maksimal Cemaran Mikroba Dalam Pangan Olahan a test has been conducted a Plate Count Test (PCA) and identyfying the existence of bacteria Salmonella typhi. The study is to find out the food safety microbiological bye measuring microbial contaminatio using PCA method and identification of Salmonella typhi. Using PCA method and identyfying the the existence of bacteria Salmonella typhi with selective media Salmonella Sgigella Agar (SSA) and gram staining. Identified 2 from 7 chilli sauce samples which are not qualified for quality standard of Peraturan Badan Pengawas Obat dan Makanan Nomor 13 Tahun 2019 Tentang Batas Maksimal Cemaran Mikroba Dalam Pangan Olahan and Salmonella typhi has not been found. Microbial contamination has been found on 2 samples which exceed the maximum limit and the existance of Salmonella typhi has not been discovered according to Peraturan Badan Pengawas Obat dan Makanan Nomor 13 Tahun 2019 Tentang Batas Maksimal Cemaran Mikroba Dalam Pangan Olahan.